Pelatihan Teknologi Informasi sebagai Media Promosi Produk Lokal Desa Sabron Sari untuk Pengembangan Ekonomi Masyarakat Desa melalui BUMKam: Information Technology Training as a Promotional Media Local Product from Sabron Sari Village for the Economic Development of the Village Community through BUMKam - Zulfiana T, Indah Sari; Lado, Meity L H; Zebua, Mercyana Trianne; Iriytanto, Santje M (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Sabron Sari Village has superior local products in the form of fruit, where most of the village people earn their living as breeders (laying hens) and fruit farmers (rambutan and duku), which are maintained and planted in the yards of each villager's house. This potential can be utilized to support the economic progress of village communities by using information technology in promotion and marketing. The objectives of this activity are for partners to know about managing/storing local products that are perishable so that the marketing process can continue when the harvest is finished, partners can use simple graphic design applications as tools for carrying out promotional designs, and partners have the knowledge and ability to run social media as an online-based promotional and marketing medium to be able to expand marketing areas. The method used is ABCD (Assets Based Community Development), which involves the development of human assets in managing natural resources in the form of fruit through socialization and training. As a result of the activity, results showed that the training participants had knowledge in storing and preserving fruit, could use simple graphic design applications and social media for promotional purposes, and could run social media as promotional and marketing media.